Modeling User Perception of Interaction Opportunities for Effective Teamwork - Kamar, Ece; Gal, Ya’akov; Grosz, Barbara J. (In Proceedings of IEEE SocialCom 2009, 2009)
This paper presents a model of collaborative decision-making for groups that involve people and computer agents. The model distinguishes between actions relating to participants’ commitment to the group and actions relating to their individual tasks, uses this distinction to decompose group decision making into smaller problems that can be solved efficiently. It allows computer agents to reason about the benefits of their actions on a collaboration and the ways in which human participants perceive these benefits. The model was tested in a setting in which computer agents need to decide whether to interrupt people to obtain potentially valuable information. Results show that the magnitude of the benefit of interruption to the collaboration is a major factor influencing the likelihood that people will accept interruption requests. They further establish that people’s perceived type of their partners (whether humans or computers) significantly affected their perceptions of the usefulness of interruptions when the benefit of the interruption is not clear-cut. These results imply that system designers need to consider not only the possible benefits of interruptions to collaborative human-computer teams but also the way that such benefits are perceived by people.